A nanofibrous membrane loaded with doxycycline and printed with conductive hydrogel strips promotes diabetic wound healing in vivo. (15th October 2022) - Cao, Wangbei; Peng, Shiqiao; Yao, Yuejun; Xie, Jieqi; Li, Shifen; Tu, Chenxi; Gao, Changyou
Abstract: Patients with diabetes suffer from a variety of complications and easily develop diabetic chronic wounds. The microenvironment of diabetic wounds is characterized by an excessive amount of reactive oxygen species (ROS) and an imbalance of proinflammatory and anti-inflammatory cells/factors, which hinder the regeneration of chronic wounds. In the present study, a wound dressing with immunomodulation and electroconductivity properties was prepared and assayed in vitro and in vivo . [2-(acryloyloxy) ethyl] Trimethylammonium chloride (Bio-IL) and gelatin methacrylate (GelMA) were 3D printed onto a doxycycline hydrochloride (DOXH)-loaded and ROS-degradable polyurethane (PFKU) nanofibrous membrane, followed by UV irradiation to obtain conductive hydrogel strips. DOXH was released more rapidly under a high ROS environment. The dressing promoted migration of endothelial cells and polarization of macrophages to the anti-inflammatory phenotype (M2) in vitro . In a diabetic rat wound healing test, the combination of conductivity and DOXH was most effective in accelerating wound healing, collagen deposition, revascularization, and re-epithelialization by downregulating ROS and inflammatory factor levels as well as by upregulating the M2 macrophage ratio. Statement of significance: The microenvironment of diabetic wounds is characterized by an excessive amount of reactive oxygen species (ROS) and an imbalance of proinflammatory and anti-inflammatory cells/factors, which hinder the regeneration of chronic wounds. Herein, a wound dressing composed of a DOXH-loaded ROS-responsive polyurethane membrane and 3D-printed conductive hydrogel strips was prepared, which effectively accelerated skin regeneration in diabetic wounds in vivo with better epithelialization, angiogenesis, and collagen deposition. DOXH regulated the dysfunctional wound microenvironment by ROS scavenging and polarizing macrophages to M2 phenotype, thereby playing a dominant role in diabetic wound regeneration. This design may have great potential for preparing other similar materials for the therapy of other diseases with excessive inflammation or damage to electrophysiological organs, such as nerve defect and myocardial infarction. Graphical abstract: Image, graphical abstract